Pengaruh Harga Diri dan Kepercayaan Diri terhadap Psychological Well Being Pasien Kanker Serviks Post Histerektomi di RS Dr. Cipto Mangunkusumo Jakarta - Robertus Surjoseto; Devy Sofyanty (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to examine and analyze empirically the influence of self esteem and self confidence on psychological well being cervical cancer patient post hysterectomy at RS Dr. Cipto Mangunkusumo Jakarta. The method used in this research is quantitative research while the data collection technique is done through observation, interview and questionnaires. The research design method was cross sectional and the sample size was 100 respondents using accidental sampling technique. The data of this study were collected with self esteem scale, self confidence scale and psychological well being scale with a Likert scale model. Self report technique is used in collecting instrumen data. The data collected was analyzed with a multiple regression test with the help of the Statistical Package for Social Sciences (SPSS) program 20.0 for Windows. The results of the research showed the influence of self esteem and self confidence on psychological well being is very significant, so that the level of psychological well being patient can be seen from level self esteem and self confidence. The recomendation from this study is that respondents can maintain and increase self esteem and self confidence to improve psychological well being.